Analisis Faktor-Faktor yang Mempengaruhi Pengembangan Sistem Pengukuran Kinerja, Akuntabilitas Kinerja, dan Penggunaan Informasi Kinerja (Studi Empiris pada Pemerintah Daerah di Wilayah Provinsi DIY) - , HERLINA PRIMARISANTI, Drs. Rusdi Akbar, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In Indonesia, there are many government agencies that can produce accountability or accountability reports are good. Based on a survey conducted in Yogyakarta Special Region, this study aims to empirically examine the factors - factors that influence the development of performance measurement systems, performance accountability, and use of performance information. In addition, researchers also attempted to interpret and explain the empirical evidence of institutional theory perspective (institutional theory). Institutional theory is used to determine the extent to which the development of performance measurement systems, performance accountability, and use of performance information is driven by the phenomenon of isomorphism (coercive, mimetic, and normative). This study uses a mixed methods approach that combines elements of quantitative and qualitative research at the same time with the sequential explanatory strategy. This study uses analysis of Partial Least Square (PLS) to test the hypothesis. This study provides evidence that training, incentives, and decision-making authority and a significant influence on the development of performance measurement systems, performance accountability, and use of performance information. Contribution of this study is to provide an understanding of the factors that influence the development of performance measurement systems, performance accountability, and use of performance information that can be used to enhance and improve performance measurement systems in government agencies.